2019
DOI: 10.1186/s41610-019-0134-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of climate change on plant invasion in the Republic of Korea

Abstract: Background: Invasive plant species are considered a major threat to biodiversity, ecosystem functioning, and human wellbeing worldwide. Climatically suitable ranges for invasive plant species are expected to expand due to future climate change. The identification of current invasions and potential range expansion of invasive plant species is required to plan for the management of these species. Here, we predicted climatically suitable habitats for 11 invasive plant species and calculated the potential species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 34 publications
7
45
0
Order By: Relevance
“…In case of a forest fire, S. elaeagnifolium could colonize the burnt bare land (Roche 1991) as an invading species and could dominate the area competing the local pioneer tree species. Under the current and future climatic scenarios, plant species that are tolerant to abiotic stress (heat, drought), such as S. elaeagnifolium, are expected to have an advantage over species that are more sensitive to these factors (Christodoulakis et al 2009, Uludag et al 2016, Adhikari et al 2019). In the context of climate change, especially in hot and dry Mediterranean areas, and the expected increase in disturbances in forest canopies, studies on demographic traits of this invasive alien species are important for the survival of forest ecosystems in the future.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
See 1 more Smart Citation
“…In case of a forest fire, S. elaeagnifolium could colonize the burnt bare land (Roche 1991) as an invading species and could dominate the area competing the local pioneer tree species. Under the current and future climatic scenarios, plant species that are tolerant to abiotic stress (heat, drought), such as S. elaeagnifolium, are expected to have an advantage over species that are more sensitive to these factors (Christodoulakis et al 2009, Uludag et al 2016, Adhikari et al 2019). In the context of climate change, especially in hot and dry Mediterranean areas, and the expected increase in disturbances in forest canopies, studies on demographic traits of this invasive alien species are important for the survival of forest ecosystems in the future.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
“…The understanding of the distribution dynamics of invasive alien plant species under predicted climate change could contribute to an effective management and conservation of ecosystems in the future (Thapa et al 2018), as the response of invasive plants to climate change may increase their ability to establish and alter Mediterranean ecosystem processes and function (Phillips et al 2019, Langmaier & Lapin 2020. As invasive plants native to tropical countries can thrive under higher temperatures they could consequently displace native species under the warming climate change conditions (Adhikari et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…All of the above reasons reinforce the possibility of habitat expansion of these species under future climate change scenarios. Similarly, some ecological modeling on drought-friendly species such as Capparis spinosa L. (Ashraf et al, 2018), Ambrosia artemisiifolia L. (Adhikari et al, 2019), Ambrosia trifida L. (Adhikari et al, 2019), and Solanum carolinense L. (Adhikari et al 2019) confirmed these results. Additionally, climate change can alter the competitive interactions and species composition within communities (Howden et al, 2003).…”
Section: Discussionmentioning
confidence: 52%
“…The distribution models generated in this study, based only on climatological variables, assess the effect of climate change on the current and future distribution of OWSF. Several publications have used only the climatic variables for this purpose [54][55][56][57][58][59] . Incorporating other environmental variables such as human population, land cover, vegetation index, host animal distribution, etc, could improve the resultant models.…”
Section: Discussionmentioning
confidence: 99%